Took a licking, kept on ticking [Internet security]. - Cherry, S.M (IEEE spectrum)
A mysterious assault on its root server system left the Internet unscathed, but chastened. At almost exactly 9 p.m. GMT on 21 October, the Internets 13 root servers started to receive about 10 times their normal traffic. Unknown digital assailants had taken control of other machines on the Internet, making them send a flood of packets that threatened to overwhelm the root servers. Had the attack succeeded, the Web and e-mail would have gradually become unusable. While four of the servers, all in the United States, saw virtually no disruption, the other nine, including the three overseas, failed to respond to legitimate queries for at least a few minutes. The people who run the domain name system say they learned a lot from the October episode. They want lower-level name servers to do even more caching, perhaps of the entire root server database, and for longer than two days. Root server operators also must make sure their own networks are in good working order.